Iowa RBA and updates, February 10-19, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA updates for February 10 and February 17, 1997. Highlights of the two updates include the continued presence of a Pinyon Jay and sightings of Great Gray Owls, a Ferruginous Hawk, Snowy Owls, a Prairie Falcon, and Red Crossbills. Also included are additional brief updates from February 12, 15, and 19, 1997, with more details on the Great Gray Owl and Ferruginous Hawk as well as sightings of Greater Scaup, a Peregrine Falcon, and Pine Siskins. Epson - sheet feed/flatbed